Analisis Keberlanjutan Lahan Sawah di Subak Yeh Sumbul, Desa Yeh Sumbul, Kecamatan Mendoyo, Kabupaten Jembrana - FIGLIANA, NI PUTU BELLA; SUDARMA, I MADE; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
Analysis of Rice Land Sustainability in Subak Yeh Sumbul,  Yeh Sumbul Village, Mendoyo District, Jembrana Regency The increase in tourism growth in rural areas has resulted in rapid rice land conversion. Subak Yeh Sumbul is one of the subaks that has experienced rice land conversion due to tourism growth in Bali. This subak has experienced a drastic rice land conversion of around 75 ha from a total of 190 ha since 1995 to date. This study aims to analyze the sustainability of the rice lands in Subak Yeh Sumbul based on the index value and sustainability status using multidimensional scaling (MDS) analysis and the Rapfish method. The results of the MDS method of Rapfish ordination technique show that the sustainability index value of the rice lands in Subak Yeh sumbul on the environmental, institutional, and technological dimensions show a fairly sustainable status. However, the economic and social dimensions show a less sustainable status. This shows the need for improvement in the economic and social dimensions through leveraging attributes on these dimensions to maintain the sustainable status of rice land in Subak Yeh Sumbul.